Supporting Students’ Understanding of Area Measurement Through Verknippen Applet - Wahid Yunianto (SEAMEO Regional Centre for QITEP in Mathematics, 2015)
In this paper, we will present a case study of the possibility of using an applet in the teaching and learning of area measurement. The researcher investigated how an applet can support students’ understanding of the concept of conservation of area. Data were collected through video registration, students’ work and interviews. Students were involved in six meetings around the learning of area measurement. In some meetings, students worked on hands-on activities. For instance, through cut and paste activities, students would acquirethe concept of conservation of area. They witnessed that if there is no part thrown away when cutting and pasting a figure, the area will not change. However, when it comes to reshaping a figure into another one (rectangle), students would use trial and error. Some students would face difficulties reshaping the figures into a rectangle. They could not undo their cutting when they failed in making a rectangle. To some extent, hands-on activities will constrain students. The use of an applet which provides the same activities will help students to be more creative in reshaping a figure. The school has no internet facilities to access the applet. To see the possibilities of an applet to support students understanding, after some weeks, we invited students to play with the applet. We recorded students’ activities in working with the applet. Students were enthusiastic to try when they could not solve the problems. After the session with the applet, students worked on similar problems on paper. They successfully dealt with the problems. It reveals that students prefer to use the applet because they can easily try again when they fail. It shows that students could understand how to measure areas of irregular figures.